Efektivitas Model Pembelajaran Kooperatif Think Pair and Share terhadap Motivasi dan Hasil Belajar IPA Siswa Kelas VII SMP - Yufita Sari Zega; Desman Telaumbanua (Program Studi Pendidikan Biologi - Universitas Nias, 2024)
Low student motivation and poor science learning outcomes at the junior high school level have remained persistent challenges, particularly when classroom instruction has been dominated by conventional approaches that fail to actively engage students. This study aimed to analyze the effectiveness of the Think Pair and Share (TPS) cooperative learning model in improving the motivation and science learning outcomes of seventh-grade junior high school students on the topic of Ecosystems. The study employed a Classroom Action Research (CAR) approach based on the Kemmis and McTaggart model, conducted in two cycles consisting of planning, action, observation, and reflection stages. The research subjects were 26 seventh-grade students of SMP Negeri 5 Namohalu Esiwa. Data were collected through classroom observation, learning motivation questionnaires, achievement tests, and interviews, then analyzed using descriptive quantitative and qualitative techniques. The findings revealed that the implementation of TPS significantly improved the quality of the learning process, student motivation, and learning outcomes. Student participation increased from 72.22% in Cycle I to 94.27% in Cycle II, learning motivation rose from 73.50% to 93.13%, while the average learning achievement score improved from 70.02 to 85.04, with classical mastery reaching 92.31%. These findings demonstrate that TPS was effective in creating interactive, collaborative, and meaningful science learning experiences.